2010
DOI: 10.1073/pnas.0912540107
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic m1 muscarinic receptors are necessary for mGluR long-term depression in the hippocampus

Abstract: To investigate the role of M1 muscarininc acetylcholine receptors (m1 receptors) in metabotropic glutamate receptor (mGluR)-mediated long-term depression (LTD), we produced mouse lines in which deletion of the m1 gene is restricted to the forebrain (FB-m1KO) or hippocampal CA3 pyramidal neurons (CA3-m1KO). Stimulation in FB-m1KO hippocampal slices resulted in excitatory postsynaptic potentials and long-term synaptic plasticity (long-term potentiation and LTD) similar to controls. The mice were deficient in (S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 28 publications
2
42
0
Order By: Relevance
“…Notably, such a hyperactivity phenotype has been associated with the lack of M 1 R on inhibitory interneurons in the striatum, where this receptor is normally activated by locally released acetylcholine, resulting in inhibitory projections to dopaminergic neurons in the substantia nigra pars compacta. 33,34 Moreover, M 1 R Ϫ/Ϫ mice showed working memory and consolidation impairment without acquisition deficit in some learning-and memory-dependent tasks. 21 The genetic deletion of M 1 R also resulted in electrophysiological deficits and intracellular signaling disruption (eg, mitogen-activated protein kinase activation and phosphoinositide hydrolysis).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, such a hyperactivity phenotype has been associated with the lack of M 1 R on inhibitory interneurons in the striatum, where this receptor is normally activated by locally released acetylcholine, resulting in inhibitory projections to dopaminergic neurons in the substantia nigra pars compacta. 33,34 Moreover, M 1 R Ϫ/Ϫ mice showed working memory and consolidation impairment without acquisition deficit in some learning-and memory-dependent tasks. 21 The genetic deletion of M 1 R also resulted in electrophysiological deficits and intracellular signaling disruption (eg, mitogen-activated protein kinase activation and phosphoinositide hydrolysis).…”
Section: Discussionmentioning
confidence: 99%
“…This reduced number of failures suggests a presynaptic site of LTP expression. A decreased failure rate has, however, also been attributed to the insertion of AMPA receptors at previously "silent" synapses (Kullmann, 1994;Isaac et al, 1995;Liao et al, 1995), albeit for NMDAR-dependent LTP.…”
Section: Ltp Induction Requires Activation Of Mglur and Machrsmentioning
confidence: 99%
“…Expression involves increases in the number and/or changes in the properties of postsynaptic AMPA receptors (AMPARs; Benke et al, 1998;Malinow and Malenka, 2002;Bredt and Nicoll, 2003). Synapses which excite hippocampal (Bliss and Lomo, 1973;Morris et al, 1986) and neocortical (Jay et al, 1995;Heynen and Bear, 2001) principal cells express Hebbian LTP. Although Hebbian LTP is conventionally presented as a glutamate receptor narrative, it is modulated by other transmitters.…”
Section: Introductionmentioning
confidence: 99%
“…2C). Recent studies have shown that the induction of DHPG-LTD in the hippocampal CA1 region relies on the activation of M 1 muscarinic receptors (Kamsler et al, 2010). We next examined a possible effect of the selective M 1 antagonist pirenzepine (75 nM) on DHGP-LTD. No change in the extent of DHPG-LTD was observed in slices from saline-treated mice (69.3 Ϯ 5.2% of baseline, n ϭ 4) (Fig.…”
Section: Dhpg-ltd In the Nac Is Mediated By Mglur5mentioning
confidence: 99%